Socioeconomic profile and agricultural practices of farmers in traditional communities of Jangada, Mato Grosso, Brazil (Revista Brasileira Multidisciplinar, 2025)
Agricultural diversity depends on natural conditions and the cultural and socioeconomic profiles of farmers. The present study aimed at assessing the socioeconomic characteristics of four contiguous traditional rural communities (Mutum, Vaquejador, Ribeirão das Pedras Acima and Quilombo) located in the municipality of Jangada, Mato Grosso, Brazil, and their effects on the preservation of agrobiodiversity. Semi-structured interviews involving at least half of all family units confirmed that small-scale agriculture was performed in all communities although Mutum presented the lowest proportion of farmers. Socioeconomic profiles of families were similar with agricultural activities conducted mainly by males of median age 56 years. Mutum showed the largest proportion of young people who had left the community (63.9 %), while Ribeirão das Pedras Acima had the highest percentage of new family units located in the same community (64.3 %). The main reasons for the departure of young people were deficient infrastructure (limited educational and health services) and inferior job opportunities.  Our results demonstrate that reassessment of public policies and educational strategies in rural communities is necessary to stimulate the appreciation of traditional agricultural knowledge and practices, and to persuade young people to remain by breaking the maxim that urban living is superior to country reality.